2000
DOI: 10.1146/annurev.soc.26.1.497
|View full text |Cite
|
Sign up to set email alerts
|

Wealth and Stratification Processes

Abstract: This paper reviews current information on wealth trends, with particular attention to the role of household wealth in the stratification system. The first section considers the relevance of wealth for stratification processes and examines why an appreciation of household wealth has been slow to materialize in stratification research. Subsequent sections discuss aspects of the distribution of household wealth in the United States, the transmission of inequality across generations, and implications of a consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
252
0
34

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(290 citation statements)
references
References 58 publications
4
252
0
34
Order By: Relevance
“…Again, this indicator for parental resources is most influential for gifts of money (Model 3), where the effect is three times larger compared to gifts of houses or land (Model 2). These findings are consistent with the literature on wealth portfolios in different social strata which has shown that home ownership is quite common even in lower strata (Kurz 2004), whereas the possession of large amounts of liquid assets is a privilege of higher strata (Spilerman 2000). The number of siblings, as expected, is negatively correlated with the chances of receiving transfers from parents.…”
Section: Resultssupporting
confidence: 91%
“…Again, this indicator for parental resources is most influential for gifts of money (Model 3), where the effect is three times larger compared to gifts of houses or land (Model 2). These findings are consistent with the literature on wealth portfolios in different social strata which has shown that home ownership is quite common even in lower strata (Kurz 2004), whereas the possession of large amounts of liquid assets is a privilege of higher strata (Spilerman 2000). The number of siblings, as expected, is negatively correlated with the chances of receiving transfers from parents.…”
Section: Resultssupporting
confidence: 91%
“…Already in the 1980, the topic was described as a "sociological lacunae" (McNamee and Miller 1989). Although there has been some more sociological scholarship on the issue in the intervening 20 years, it is far less than one would expect given the relevance of the topic (Beckert 2008;Kohli 1999;Spilerman 2000). To be sure, inheritance has not always been a neglected topic.…”
mentioning
confidence: 99%
“…Elas incluem a mobilização de redes sociais, ter famílias que permitam assumir maiores riscos, bem como outros fatores que influenciam a forma como os indivíduos participam da economia. Todavia, é muito difícil medir isso diretamente, e a maior parte da literatura que aponta nessa direção o faz por exclusão das explicações alternativas (Breen e Jonsson, 2005;Erikson e Goldthorpe, 2002;Finnie e Irvine, 2006;Piketty, 2000;Spilerman, 2000;Torche, 2014;Torche e Costa-Ribeiro, 2012;Torche e Spilerman, 2008. O que talvez seja mais importante no nosso caso é que uma dessas explicações alternativas excluídas frequentemente é a mobilidade educacional, o que indica que ter níveis elevados de educação formal sem ter as outras vantagens mencionadas pode impor um limite para o posicionamento no topo da hierarquia social.…”
Section: Estudos Anterioresunclassified